Peptidylarginine Deiminase 4 Promotes the Renal Infiltration of Neutrophils and Exacerbates the TLR7 Agonist-Induced Lupus Mice - Hanata, Norio; Shoda, Hirofumi; Hatano, Hiroaki; Nagafuchi, Yasuo; Komai, Toshihiko; Okamura, Tomohisa; Suzuki, Akari; Gunarta, I Ketut; Yoshioka, Katsuji; Yamamoto, Kazuhiko; Fujio, Keishi (Frontiers in Immunology, 2020)
Peptidylarginine deiminase 4 (PAD4), encoded by PADI4, plays critical roles in the immune system; however, its contribution to the pathogenesis of lupus nephritis remains controversial. The pathological roles of PAD4 were investigated in lupus model mice. An imiquimod (IMQ)-induced lupus model was analyzed in wild-type (WT) and Padi4-knockout (KO) mice. Proteinuria, serum anti-double stranded DNA (anti-dsDNA) antibody, and renal infiltrated cells were evaluated. Neutrophil migration and adhesion were assessed using adoptive transfer and adhesion assay. PAD4-regulated pathways were identified by RNA-sequencing of Padi4 KO neutrophils. Padi4 KO mice exhibited significant improvements in proteinuria progression compared with WT mice, whereas, serum anti-dsDNA antibody and immune complex deposition in the glomeruli showed no difference between both mice strains. Padi4 KO mice showed decreased neutrophil infiltration in the kidneys. Adoptively transferred Padi4 KO neutrophils showed decreased migration to the kidneys of IMQ-treated WT mice, and adhesion to ICAM-1 was impaired in Padi4 KO neutrophils. Padi4 KO neutrophils exhibited reduced upregulation of p38 mitogen-activated protein kinase (MAPK) pathways. Toll-like receptor 7 (TLR7)-primed Padi4 KO neutrophils demonstrated reduced phosphorylation of p38 MAPK and lower expression of JNK-associated leucine zipper protein (JLP), a p38 MAPK scaffold protein. Neutrophils from heterozygous Jlp KO mice showed impaired adhesion to ICAM-1 and decreased migration to the kidneys of IMQ-treated WT mice. These results indicated a pivotal role of PAD4-p38 MAPK pathway in renal neutrophil infiltration in TLR7 agonist-induced lupus nephritis, and the importance of neutrophil-mediated kidney inflammation. Inhibition of the PAD4-p38 MAPK pathway may help in formulating a novel therapeutic strategy against lupus nephritis.